Rizzoli & Isles. The complete fifth season [videorecording (DVD)] - Tamaro, Janet (Rizzoli & Isles ;)
Best friends and work colleagues Detective Jane Rizzoli and Medical Examiner Dr. Maura Isles use the best of their expert skills and unique personalities to solve Boston's deadliest crimes.